MEMBENTUK KARAKTER PESERTA DIDIK BERBASIS BUDAYA DALAM PENDIDIKAN AGAMA HINDU: MEMBENTUK KARAKTER BERBASIS BUDAYA - Putu Ayu Wulan Sri Diantari (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Advances in science and technology in the 21st century mean that environmental changes that affect education will be increasingly dominant. In other words, personality development and formation require exemplary development to be inherited, carried out, and strengthened consistently, and accompanied by noble values, through a continuous process of learning, training, and long-term habituation. Therefore, Hindu education can be a normative means to educate the entire personality of modern learners through local wisdom that motivates children. An important education that emerges from the interweaving of elements of Hindu religious education and cultural learning is that Hindu religious education is not rigid to change, just as there is no education and culture that does not change. Hindu religious education is also directed to build the personal mental qualities of students who are intelligent, skilled and have a religious attitude, are sensitive to changes in behavior in society, commitment to the values and principles of living harmoniously and creatively in a pluralistic society, caring for the environment and working in accordance with their swadarma